Miss Daisy is still crazy! - Gutman, Dan (Gutman, Dan. My weirdest school ;, 2016)
"When Miss Daisy returns to Ella Mentry School as a substitute teacher, the kids are in for a weird and wacky day of not learning about math, writing, the weather, and more"--